2020
DOI: 10.1063/5.0009378
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting particle dynamics in HiPIMS discharges. I. General effects

Abstract: A detailed experimental study of high power impulse magnetron sputtering processes is performed by time-resolved imaging of the ground state sputtered particles. New details related to the behavior of both neutral and singly ionized atoms are shown, as a result of separate treatment of the plasma-on and plasma-off time phases. In Paper I, the ion/neutral density redistribution in the ionization zone during sputtering is analyzed; the role of main discharge parameters, such as pulse repetition rate, pulse energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
35
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 92 publications
11
35
0
Order By: Relevance
“…However, apart from the first peak, which occurs within the time T on , further density peak(s) are sometimes observed after the end of T on . A second peak attributed to ion 3,9,10) and electron currents/densities 3,4,6,11,12) after T on was reported by previous studies.…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…However, apart from the first peak, which occurs within the time T on , further density peak(s) are sometimes observed after the end of T on . A second peak attributed to ion 3,9,10) and electron currents/densities 3,4,6,11,12) after T on was reported by previous studies.…”
Section: Introductionsupporting
confidence: 75%
“…n i increases to around 4 × 10 18 m −3 , and n e reaches 1 × 10 18 m −3 . Previous research found that two peaks of n i 3,10) and n e 3,4,6,11,12) were observed, with densities of 10 18 m −3 . One of the peaks appeared within T on and another peak appeared after the end of T on .…”
Section: Plasma Parametersmentioning
confidence: 90%
See 2 more Smart Citations
“…These techniques, which have dramatically increased the ionization degree of plasma, have attracted attention collectively as a new method, i.e., ionized physical vapor deposition (I-PVD) [11,15]. In recent years, both of these techniques have achieved an improvement in film deposition rate by introducing multi-pulsing as a deep oscillation magnetron sputtering (DOMS) [16][17][18][19][20][21][22][23][24] technique with a large number of pulses in MPPMS and as a multi-pulse HiPIMS (m-HiPIMS) [25][26][27][28][29][30][31] technique with multiple bipolar pulses in HiPIMS. Improvements in the film deposition rate through the introduction of multiple pulses are brought about due to the long-duration pulse sputtering per cycle in the former and due to the reduction of the rearward attraction for sputtered particle ions to the target in the latter.…”
Section: Introductionmentioning
confidence: 99%